Evaluating referrals between rural district hospitals and a regional hospital in South Africa - Kambola D. Ngoie; Louis Jenkins; Johann Schoevers (African Journal of Primary Health Care & Family Medicine)
Background: Efficient referral systems are essential for improving healthcare and patient outcomes, especially in resource-limited settings where access to public specialist care is limited by too few specialists, growing populations and constrained resources impacting non-emergency and emergency referrals. District hospitals (DHs) must ensure that patients receive the appropriate level of care. High-quality referral systems are necessary for the cost-effective flow of patients between district and regional hospitals (RHs).